Human sexuality and nursing practice when the topic is sex - Ducharme, Stanley H.; Concept Media, inc. (Irvine, CA : Concept Media, 1999)
Explores the nurse's role in talking with patient abiut sex, emphazing the sensitive and often anxiety-producing nature of this aspect of patient care.
#2. Human Sexuality and nursing practice
Consultants, Stanley Ducharme, et al.
Keywords: Nursing process; Sexuality; Chronic Disease; Disabled persons